The Role of the Negative 3-H Trio in Second Language Education - Chu, Jing; Zeng, Xiaoxia (Frontiers in Psychology, 2021)
Language has been proven to strongly affect different aspects on one’s life/career including his/her identity and interpersonal communication skills beyond the immediate context. Given this, now proper discourse and interlocutor’s emotions are highlighted in academia. However, few studies (if any) have explored the role of negative stressors and constructs in L2 classroom discourse and interpersonal communication competency. To fill this yawning lacuna, the present study provided a glance at the impact of three negative language aspects of hate, hurt, and harm (also called negative 3-H trio) on L2 education. Moreover, it presents the definitions, origins (positive psychology, positive peace psychology), dimensions, and applications of each aspect. Finally, some implications and future directions are suggested to avid scholars in L2 and mainstream education.